2021
DOI: 10.1101/2021.05.06.443001
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

KAI2 regulates seedling development by mediating light-induced remodelling of auxin transport

Abstract: The photomorphogenic remodelling of seedling growth upon exposure to light is a key developmental transition in the plant life cycle. The α/β-hydrolase signalling protein KARRIKIN-INSENSITIVE2 (KAI2), a close homologue of the strigolactone receptor DWARF14 (D14), is involved in this process, and kai2 mutants have strongly altered seedling growth as a result. KAI2 and D14 both act through the MAX2 (MORE AXILLARY BRANCHING2) F-box protein to target proteins of the SMAX1-LIKE (SUPPRESSOR OF MAX2 1) (SMXL) family … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…DR5v2 pro :GFP expression was decreased in kai2 meristems with respect to the wild type, possibly due to reduced rootward flow of auxin through kai2 roots. 27 Importantly, and consistent with the RHL response, DR5v2 pro -driven GFP signal in kai2-2 increases to the level of the untreated wild type after treatment with NAA but does not change with 2,4-D (Figure 3E). Together, these results suggest there may be reduced influx carrier activity in kai2.…”
Section: Reportsupporting
confidence: 71%
“…DR5v2 pro :GFP expression was decreased in kai2 meristems with respect to the wild type, possibly due to reduced rootward flow of auxin through kai2 roots. 27 Importantly, and consistent with the RHL response, DR5v2 pro -driven GFP signal in kai2-2 increases to the level of the untreated wild type after treatment with NAA but does not change with 2,4-D (Figure 3E). Together, these results suggest there may be reduced influx carrier activity in kai2.…”
Section: Reportsupporting
confidence: 71%
“…These results, coupled with the recently reported research findings from Hamon‐Josse et al . (2021), increase the adaptive mechanisms by which KL signaling integrates the auxin hormone pathway to achieve adaptation to different light conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, auxin seems to be one of the most important regulatory factors involved in the elongation of the hypocotyl during shade avoidance. A recent study showed that KAI2 controls the light‐induced remodeling of the PIN‐mediated auxin transport system in seedlings (Hamon‐Josse et al ., 2021). In summary, shade stress may regulate hypocotyl elongation by promoting auxin biosynthesis and/or transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KAI2 remodels auxin distribution in seedlings during photomorphogenesis, putatively by controlling the abundance of the auxin efflux carriers PIN1, PIN3, and PIN7 at the plasma membrane. This in turn influences hypocotyl elongation and root development ( 67 ).…”
Section: Discussionmentioning
confidence: 99%